“How Am I Doing?” Teaching Children with Emotional-Behavioral Disorders to Self-Manage Their Behaviors - Tensfeldt, Lael; Verroulx, Amory; Mahdavi, Jennifer N. (Journal of the American Academy of Special Education Professionals, 2018)
Relying on external supports to shape the behaviors of students with emotional/behavioral disorders (EBD) is risky as these classroom supports may not generalize to internal strategies that students can use independently in the community. Two special educators approached building self-determination skills in their students with EBD from different perspectives: applied behavior analysis and sensorimotor regulation. Despite different approaches, each teacher employed consistency of language, explicit instruction, and empowering students to engage in self-management. The teachers observed that after students learned to self-manage, they did so with increasing success, resulting in fewer incidences of antisocial or unproductive behavior. The strategies each teacher used are described, emphasizing practices that both used so that other special educators may follow their examples.